Supportive breeders of Atlantic salmon Salmo salar have reduced fitness in nature. Issue 9 (28th June 2019) - Jonsson, Bror; Jonsson, Nina; Jonsson, Marius
Abstract: Wild Atlantic salmon ( Salmo salar ) are in decline over the entire distribution area, and populations are enhanced by supportive breeding. Parental fish are sampled in rivers, crossed and the offspring reared in hatcheries until smolting when released, ready for ocean migration. Naturally reproducing salmon entering the River Imsa from the ocean were monitored from 1976 through 2013, and since 1982, supportive breeders spawning in the river were also monitored. The supportive breeders were first‐generation salmon, reared for 1—2 years in a hatchery before being released at the mouth of the river so they could migrate to sea (i.e., sea‐ranching). Wild and sea‐ranched salmon live in the ocean for 1—2 years before they return to the river for spawning. In years when only wild adults were present, mean number of smolts produced per 100 m 2 river area and female breeder was 0.47. When there were 5% wild females, the mean production was only 0.088 (19%). The gradual decrease in offspring production with decreasing proportion of wild females ( r 2 = .41) indicates that the reduced offspring production was caused by inferior spawning behavior of hatchery females or reduced survival of their offspring in nature. Previous experimental evidence suggests that wild males fertilize the eggs of wild but also hatchery females. It is discussed how epigenetic effects caused by hatchery environments influence the developing juveniles, lead to phenotypic changes that may reduce their fitness in nature even after free ranging for a year or more in the ocean before they return and spawn.